The Impact of Structural Changes on Sound Pressure Levels in a Neonatal Intensive Care Unit - Carlos CARVALHAIS; Célia RODRIGUES; Ana XAVIER; Manuela V. SILVA; Joana SANTOS (Archives of Acoustics)
The design of neonatal intensive care units (NICU) influences both patient safety and clinical outcomes as well as the acoustic conditions. In NICU exposure to sound pressure levels above the recommended can affect both neonates and healthcare staff.